Extreme weather and high-level PM2.5 co-exposure are associated with elevated respiratory syncytial virus circulating intensity - Jingyi Liang; Rodrigo Fasce; Saturnino Luz; You Li; Harish Nair (Communications Health, 2026)
Abstract Background Higher temperatures and more frequent heat waves and cold spells due to climate change raise concerns for respiratory health. However, the association of extreme temperature events with RSV epidemics remains unclear. Method We conducted time-series analyses to assess relative risks from exposure to extreme temperatures alone and joint exposure to extreme temperatures and high-level particulate matter [2.5 microns or less in diameter ( $${{{\rm{PM}}}}_{2.5}$$ PM 2.5 )] pollution on RSV circulating strength. Japan and Chile were selected as two contrasting settings with distinct climatic and geographic backgrounds. Weekly data on laboratory-confirmed RSV-positive cases, denominator population, meteorological factors, and air pollutants were collected from 16 Chilean regions (2015–2018) and 47 Japanese prefectures (2013–2019). We fitted quasi-Poisson regression to assess the local-level estimates and used random-effects meta-analyses to obtain national estimates. Results Here we show that heat waves are linked to increased RSV circulating intensity in Japan, with relative risks up to 1.49 (95% confidence interval (CI): 1.29–1.73). Cold spells show weaker but positive effects. Although cold spells demonstrate no consistent effects in Chile, joint exposure to high-level $${{{\rm{PM}}}}_{2.5}$$ PM 2.5 pollution and cold spells increases risks by 32% (95% CI: 1.10–1.58). Joint exposure to high-level $${{{\rm{PM}}}}_{2.5}$$ PM 2.5 pollution and heat waves raises risk by up to 66% (95% CI: 1.27–2.16) in Japan. Conclusions These findings reveal national patterns and regional variations in RSV responses to extreme temperatures, highlighting the need for public health measures targeting modifiable population-level factors amid global climate change.